ASSUMPTIONS. - Bennett, George E. (The Accounting Review, 1933)
Abstract The article illustrates through an example in a coaching class the fallacies of assumptions in problem solving demonstrations by teachers of accounting. An experience of many years as an accounting teacher plus an experience of some years as an examiner for the licensing of accountants has convinced the author that the fallacy of assumption is one of the things responsible for the heavy toll exacted of the candidates who attempt professional examinations. Apparently, assumption is believed to provide an easy, or lazy person's way out of what seems to be at least at first glance a perplexing situation. A trial balance given in a problem does not balance. This fact alone affords no reason for the student or candidate assuming that the difference must be adjusted through some account like notes or accounts payable, or through some other account as far fetched. Perhaps a careful study of the situation will show that the requirements may be met almost completely by ignoring the discrepancy.